ISOLASI DAN KARAKTERISASI ENZIM b-1,3-ENDOGLUKANASE DARI TANAMAN KUBIS (Brassica oleracea cv. Capitata L.) - Y. Sri Wulan Manuhara (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2010)
Isolation and characterization of β-1,3-endoglucanase from cabbage (Brassica oleracea var. capitata L.) have been done. It showed 40° C of optimum temperature, and optimum pH is 7. After the purification with hydrophobic interaction chromatography and ion exchange chromatography, it’s activity was increased. Based on SDS-PAGE analysis, β-1,3-endoglucanase have molecular weight around 48 kD. Antifungal activity of β-1,3-endoglukanase show that it has best inhibition zone on Fusarium solanii at extract from ion exchange chromatography.